2019
DOI: 10.1097/md.0000000000014898
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high impact exercise intervention on bone mineral density, physical fitness, and quality of life in postmenopausal women with osteopenia

Abstract: Osteoporosis and osteopenia prevailed in postmenopausal women and predisposed to osteoporotic fractures that increase mortality, morbidity, and the cost of social care. Here, we investigated the effect of 24 weeks of aerobic dancing on the bone miner density, physical fitness and health-related quality of life (HRQoL) in postmenopausal women with osteopenia. Total 80 participants (control [CON]: 40; exercise [EX]: 40) were included in the final analysis. The EX group underwent a 24-week aerobic dance intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 27 publications
0
32
0
1
Order By: Relevance
“…It may also be that our participants did not engage in specific bone‐loading activities. Intervention studies show that regular physical activity several times a week is effective in increasing femoral neck BMD in women during their postmenopausal years . However, to induce osteogenic effects on the femoral neck, intensive physical exercise such as brisk walking, running and jumping, or high‐load resistance training targeting the hip region is required.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be that our participants did not engage in specific bone‐loading activities. Intervention studies show that regular physical activity several times a week is effective in increasing femoral neck BMD in women during their postmenopausal years . However, to induce osteogenic effects on the femoral neck, intensive physical exercise such as brisk walking, running and jumping, or high‐load resistance training targeting the hip region is required.…”
Section: Discussionmentioning
confidence: 99%
“…However many women are searching for different, alternative methods to reduce the severity of menopausal symptoms [5,6]. Nonpharmaceutical intervention such as physical activity was proven to be an effective method of reducing menopausal symptoms, decreasing bone loss and increasing muscle strength in menopausal women [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Other study suggested that higher doses of impact exercise attenuated natural age-related declines in total bone mineral density in postmenopausal women [18]. Physical activity, especially aerobic dance, was proven as an effective and efficient method in improving health, physical function and physical fitness in postmenopausal women [8]. The systematic review and meta-analysis published in 2018 recommended yoga for menopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that, 24-week aerobic dance intervention could result in the lower the incidence of bone fracture through increasing BMD and decreasing fall risk for postmenopausal women. Grip strength, sidestep and physical functional domain of HRQoL in the exercise group were significantly improved compared to the contol group (26). Another single-blind randomized controlled prospective trial study (92 postmenopausal women) was consistent of 3 groups: First group of patients with exercises and physical modalities (gr.…”
Section: Effects Of Physical Activitymentioning
confidence: 94%